Determinants of postnatal care non-utilization among women in Demba Gofa rural district, southern Ethiopia: a community-based unmatched case-control study - Manote, Markos (BMC Pregnancy Childbirth, 2020)
BACKGROUND: Maternal and neonatal mortality remain a significant problem across much of the developing world, especially in sub-Saharan Africa countries. In Ethiopia, most maternal and neonatal deaths occur during the postpartum period; this is a critical time for monitoring the health of women and newborns, but the most neglected period for care. In rural communities of Ethiopia, the utilization of postnatal care service is very low and evidence on which factors contribute to the non-utilization of postnatal care (PNC) is insufficient. Consequently, this study was designed to identify the determinants of postnatal service non-utilization among women who gave birth in Demba Gofa rural district, Southern Ethiopia. METHODS: A community-based unmatched case-control study was conducted among 186 cases (postnatal care non-utilizers) and 186 controls (postnatal care utilizers) in Demba Gofa rural district from March 1 to April 10, 2019. A previously tested interviewer-administered structured questionnaire was used for data collection. Binary logistic regression analysis was performed. In the final multivariable logistic regression analysis model, a p-value of less than 0.05 and an Adjusted Odd Ratio (AOR) with a 95% confidence interval (CI) was used to determine variables for postnatal care non-utilization. RESULTS: In this study, women who delivered recently were incorporated within 186 cases and 186 controls. Not knowing the availability of PNC services (AOR: 4.33, 95% CI: 1.71–10.99), having a home delivery (AOR: 7.06, 95% CI: 3.71–13.44), ANC non-attendance (AOR: 6.14, 95% CI: 3.01–12.50), unable to make an independent decision (AOR: 9.31, 95% CI: 3.29–26.35), and not participating in the Women’s Development Army (WDA) (AOR: 5.09, 95% CI: 2.73–9.53) comprised the determinants which were assessed for non-utilization of postnatal care services. CONCLUSIONS: Encouraging institutional delivery along with integrated health education about postnatal care and postnatal danger signs, empowering women to execute independent decisions, accessing PNC services and strengthening participation in the Model Families will likely improve postnatal care service utilization in the district of Ethiopia.